The Mediating Role of Perceived Value on Purchase Decisions In Ecommerce - Amin, Ahmad Muslich; Fadhilah, Muinah; Cahyani, Putri Dwi (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to find out whether brand image and digital marketing variables influence purchasing decisions on the Lazada application with perceived value as a mediating variable. This research took samples from consumers in Indonesia. The sampling method is non-probability, and the sampling technique uses purposive sampling. Data collection was carried out via messages with questionnaires sent via WhatsApp. The number of respondents processed was 112 respondents and the data was analyzed using SPSS. The results of the t test research show that the brand image variable has a significant effect on purchasing decisions with a significance value of 0.013 <0.05; The digital marketing variable has no influence and is not significant on purchasing decisions with a significance value of 0.072 > 0.05; The perceived value variable has a significant effect on purchasing decisions with a significance value of 0.000 <0.05; The brand image variable has a significant effect on perceived value with a significance value of 0.002 <0.05; The digital marketing variable has a significant effect on perceived value with a significance value of 0.002 < 0.05. Based on the results of the F test, the variables brand image, digital marketing, and perceived value have a simultaneous influence on the purchasing decision variable, because the significance value is 0.000 < 0.05; The brand image and digital marketing variables have a simultaneous effect on perceived value, because the significance value is 0.000 <0.05.